Contribuição para o conhecimento do gênero Chironomus Meigen, 1803 na região neotropical - Correia, Leny Célia da Silva (Universidade Federal de São Carlos, 2004)
The present work aimed to study one of the most used genera in water quality assessment, Chironomus, identifying and/or describing the species inhabiting aquatic systems of the State of São Paulo with varied ecological features. The study area included 27 aquatic systems consisting of lentic habitats (lakes, reservoirs, temporary pools, waste stabilization lagoons and fish ponds) and lotic habitats (streams, rivers and drainage channels) at different localities of Mogi-Guaçu and Tietê-Jacaré hydrographic sub-basins. The sampling and analyses followed the conventional methods used in taxonomic and limnological studies. The survey resulted in the identification of 16 Chironomus species, including 7 new records to the State of São Paulo and 8 new species. Besides C. sancticaroli Strixino & Strixino, 1981, a species previously recorded in the State of São Paulo, I identified the immatures and adults of C. calligraphus Goeldi, 1905, C. gigas Reiss, 1974, C. latistylus Reiss, 1974, C. paragigas Reiss, 1974, C. strenzkei Fittkau, 1968, C. stigmaterus Say, 1823 and C. columbiensis Wülker et al., 1989. Some species were sampled in similar habitats, indicating a possible relation with them. C. gigas, C. paragigas and C. latistylus were collected only in lentic systems with low antropic influence. The immatures of C. sp. 1, C. sp. 5 and C. sp. 6 were sampled only in association with aquatic macrophytes growing in lakes and stream pools. C. sp. 3 and C. sp. 4 inhabited temporary pools with great amounts of detritus. C. stigmaterus and C. calligraphus were found only in waste stabilization lagoons. Only the larvae of C. sp. 2 were sampled in lotic systems polluted with high level of organic material from urban sewage and agricultural activities. The morphological analyses of larvae enabled the construction of a preliminary identification key for the species of Chironomus that live in the different aquatic systems of the State of São Paulo. This key could be a useful tool in analyses and diagnostics carried out during water quality assessment programs.
Keywords: Chironomidae; Chironomidae neotropical; Diptera; Chironomus; Inseto; CIENCIAS BIOLOGICAS::ECOLOGIA